EP889 Improved cytoreduction of ovarian cancer using CD24-targeted fluorescence image-guided surgery in a preclinical murine model. (1st November 2019) - Kleinmanns, K; Fosse, V; Davidson, B; Bjørge, L; McCormack, E
Abstract : Introduction/Background: Intraoperative tumour-specific fluorescence imaging enables visualisation of cancer lesions, 1 and benefits staging and debulking of ovarian cancer. 2 In patients with advanced epithelial ovarian cancer (EOC), the completeness of cytoreduction significantly impacts prognosis. 3 We have demonstrated that EOC cell lines express high levels of the stem cell marker CD24. To improve the degree of cytoreduction in EOC, we aim to develop a near-infrared (NIR) fluorescence image-guided surgery (FIGS) protocol, using CD24-targeting probes in orthotopic xenograft and patient-derived xenograft (PDX) models. Methodology: OV90 luc+ and patient-derived EOC cells were injected orthotopically into immunodeficient NSG mice, and tumour growth was monitored by bioluminescence imaging and physical examination until metastatic disease had established. The monoclonal antibody CD24 was conjugated to the NIR fluorophore AlexaFluor750, and injected intravenously into the xenograft and PDX models 48hrs prior to surgery. Survival debulking surgery was performed, using a FIGS camera system for real-time NIR fluorescence-guided resection of tumour tissue. To evaluate the effect of FIGS, mice ( n =16) were operated under fluorescence guidance, and the other half had standard bright light surgery. Resected tumour volume, post-surgical imaging and post-operative survival were measured. Results: CD24-targeted FIGS allows for improved detection of tumour tissue and metastatic spread with high sensitivity and specificity in OV90 luc and PDX models, compared to standard bright light surgery, leading to improved resection rates and improved outcome in these preclinical murine models. Conclusion: The EOC biomarker CD24 conjugated to AlexaFluor750 demonstrates high sensitivity and specificity of tumour lesion detection in a preclinical murine model. CD24 is a promising agent for clinical implementation of fluorescence image-guided surgery in patients with ovarian cancer. Disclosure: Nothing to disclose.